Sensibilität von Seefischen an Bord. Teil 3: Untersuchungen an demersalen Fischarten der Barentssee - Kuhlmann, Holmer; Münkner, Werner; Oehlenschläger, Jörg (2001)
In previous papers the sensibility of pelagic and demersal fishes caught at depth of up to 80 m was reported. This paper deals with the sensitiveness of flatfishes, gadids, and redfish caught at depth between 260 and 450 m and with trawling times between 1 and 6 h. The sensitiveness of the fishes was tested according to the method described in previous publications (Münkner et. al. 1998) after 10 min keeping in running sea water and after 1h bulk storage respectively. The sensitiveness of the fishes increased from cod to saithe to haddock. Surprisingly American plaice and Greenland halibut turned out to be very sensitive, far more sensitive than plaice and dab caught at lower depths in the North Sea. This was indicated by the high amount of animals showing rigor already after a trawling time of 2 hand 10 min of keeping in seawater. After 1 h of bulk storage and increasing trawling time sensitiveness of all fishes decreased, as expected, significantly. Besides mechanical encroachments the main problem for the fishes caught at greater depths was the gas supersaturation in the blood and tissue causing blockage of the gill capillary vessels, exophthalmus, visible gas bubbles in the skin and eyes, and in some cases protusion of the intestines through the snout due to rapid dilatation of the swimbladder. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery Research in 2010.